Towards a Canada Post-Secondary Education Act? - Hug, Sébastien (Université d'Ottawa / University of Ottawa, 2011)
The transition from an industrial to a global knowledge-based economy has put universities in the spotlight of public policies as the new drivers of innovation and sustained economic growth. Consequently, societal expectations towards the academic community have changed and so has, under the influence of neo-liberal ideas, the public governance of higher education. This is particularly true in federalist systems, such as Germany, Australia and the European Union, where the roles of each government level in governing the higher education sector had to be renegotiated and clarified. In Canada, however, despite repeated recommendations by policymakers, scholars and international organisations, the respective responsibilities have not yet been clarified and, to date, there are still no mechanisms to coordinate the post-secondary education policies of the federal and provincial governments. This paper inquires into the reasons for this exception. In the academic literature, this has generally been explained in terms of Canada’s uniqueness with respect to its federalist system and the decentralized higher education sector. We attempt to go beyond this traditional federalism, state-centered approach, which is predominant in the Canadian higher education literature. Instead, based on interviews and official documents and inspired by the Advocacy Coalition Framework (ACF), we shall be looking at the belief systems of the major actors in the policy process and the degree of coordination among them. Our analysis comes to the conclusion that, on the one hand, proponents of a pan-Canadian approach are divided over their fundamental beliefs regarding the compatibility of inclusiveness and excellence. Some argue that the federal government must legislate common standards to ensure equal opportunities for all Canadians. Others propose a New Governance-inspired approach to create a differentiated and competitive university sector that meets the demands of the global knowledge-based economy more efficiently. On the other hand, even though the provinces differ in their beliefs regarding the equal opportunity versus economic efficiency debate, they share the same strong belief with respect to the role of the federal government. According to this view, post-secondary education is exclusively a provincial responsibility and the role of the federal government is solely to help them ‘fix the problems’. Moreover, contrary to the proponents of more intergovernmental collaboration, the provinces have successfully strengthened the coordination among themselves to block further perceived federal intrusions into provincial jurisdiction. We come to the conclusion that the absence of intergovernmental mechanisms to govern post-secondary education is a consequence of the diverging belief systems and the establishment of formal coordination structures among the provinces to block – as they perceive - further federal intrusions. Also, there is less of a sense of urgency to act compared to, say, health care. Finally, remembering the near-separation of Quebec in 1995, there is very little appetite to reopen the constitutional debates. Therefore, based on our analysis, we argue that contrary to suggestions by some higher education scholars, the establishment of intergovernmental coordinating mechanisms appears unlikely in the near future.
Keywords: Canadian higher education; Canadian federalism; Advocacy Coalition Framework; Canada Post-Secondary Education Act